Archaeology and ancient religion in the American midcontinent - Koldehoff, Brad H.; Pauketat, Timothy R. (Archaeology of the American South: New Directions and Perspectives Ser, 2018)
Intro -- Contents -- List of Illustrations -- Preface by Brad H. Koldehoff and Timothy R. Pauketat -- Introduction: An Archaeology of Ancient Religious Practices by Brad H. Koldehoff and Timothy R. Pauketat -- 1. From Tubes to Platforms: Transformations in Early Smoking Pipes and Ancient Rituals by Brad H. Koldehoff and Kenneth B. Farnsworth -- 2. From Caches to Gatherings: The Relationality of Intentionally Deposited Objects in Mississippian Buildings by Melissa Baltus -- 3. Magic Plants and Mississippian Ritual by Kathryn E. Parker and Mary L. Simon -- 4. The People of Mound 72: Ritual and Death, Integration and Community Building at Early Cahokia by Kristin M. Hedman and Eve A. Hargrave -- 5. Putting Religion Ahead of Politics: Cahokian Origins as Viewed through Emerald's Shrines by Susan M. Alt -- 6. A Landscape of Mounds: Community Ethnogenesis at Aztalan by John D. Richards and Thomas J. Zych -- 7. The Power of Place: Ancient Ritual Landscapes in Southwestern Illinois by Mark J. Wagner, Jonathan Remo, Kayeleigh Sharp, and Go Matsumoto -- 8. Ancient Skywatchers of the Eastern Woodlands by William F. Romain -- Contributors -- Index